Coronary Artery Disease in Chronic Kidney Disease: Need for a Heart–Kidney Team-Based Approach - Gautam R Shroff; Michelle D Carlson; Roy O Mathew (European Cardiology Review)
Chronic kidney disease and coronary artery disease are co-prevalent conditions with unique epidemiological and pathophysiological features, that culminate in high rates of major adverse cardiovascular outcomes, including all-cause mortality. This review outlines a summary of the literature, and nuances pertaining to non-invasive risk assessment of this population, medical management options for coronary heart disease and coronary revascularisation. A collaborative heart–kidney team-based approach is imperative for critical management decisions for this patient population, especially coronary revascularisation; this review outlines specific periprocedural considerations pertaining to coronary revascularisation, and provides a proposed algorithm for approaching revascularisation choices in patients with end-stage kidney disease based on available literature.